Socio-economy and Related Factors Influencing Condition and Capacity of Human Excreta Disposal and Sewer Systems: A Case Study in Coastal City of Manado - Kandou, Grace Debbie; Lusut, Markus T. (Kesmas, 2010)
Di Manado, limbah cair yang tidak diolah dari rumah tangga termasuk dari kakus dan dari aktivitas-aktivitas lain yang menghasilkan limbah cair seperti rumah makan, hotel, rumah sakit, tempat pembuangan akhir sampah, dan pasar dibuang langsung ke Teluk Manado melalui selokan dan sungai. Kondisi ini diperparah oleh kapasitas kakus yang tidak memadai dan saluran pembuangan limbah cair yang buruk. Untuk menilai faktor-faktor yang mempengaruhi kondisi dan kapasitas sistem pembuangan yang mungkin mengakibatkan penurunan derajat kesehatan dan lingkungan, telah dilakukan kajian deskriptif di dua kecamatan di Kota Manado yang melibatkan 304 rumah tangga di Wenang dan 300 rumah tangga di Molas. Ditemukan bahwa kebanyakan rumah tangga di kedua kecamatan tersebut telah memiliki toilet, masing-masing sebanyak 83,2% di Wenang dan 75,0% di Molas. Namun, tidak ada toilet yang berteknologi modern melainkan hanya menggunakan lubang dalam, saluran terbuka, dan sungai. Akibatnya, selama tahun 2002 kasus-kasus diare mencapai 1.250 di Wenang dan 513 di Molas. Di Molas, kejadian dematitis, gastritis, dan tifoid masing-masing mencapai 1.618. 272 dan 10 kasus. Secara statistik, kondisi dan kapasitas septic tank berhubungan dengan pendidikan formal dan pengetahuan mengenai limbah cair. Untreated wastewater containing human excreta from households as well as from other wastewater-generating sources such as restaurants, hotels, hospitals, garbage disposal, and markets, is discharged directly into Manado Bay through ditches, sewers, canals, and rivers. This situation is exacerbated by inadequate capacity of human excreta disposal treatment and improper sewage system. To assess factors influencing condition and capacities of this system that may degrade human health and the environment, a descriptive study has been conducted in two districts of the City of Manado. This study involved 304 households in Wenang and 300 households in Molas district. It was found that most households in those districts have their own toilet, 83.2% and 75.0% in Wenang and Molas respectively. However, no modern technology had been adopted where open deep holes, ditches, sewers, or rivers were still being used for toilets, particularly by low income communities. During 2002 there were 513 and 1,250 diarrhoea cases reported in Molas and Wenang respectively. In Molas 1,618 dermatitis cases, 272 gastritis cases, and 10 typhoid cases were also reported. Statistically, the condition and capacity of residential septic tank were significantly correlated with the residents’ level of formal education and wastewater-related knowledge.